Varroa destructor resistance to tau‐fluvalinate: relationship between in vitro phenotypic test and VGSC L925V mutation. Issue 12 (14th September 2022) - Almecija, Gabrielle; Schimmerling, Marion; Del Cont, Aurélie; Poirot, Benjamin; Duquesne, Véronique
Abstract: BACKGROUND: Varroa destructor is a parasitic mite of the honey bee, Apis mellifera . Its presence in colonies can lead to a collapse within a few years. The use of acaricides has become essential to manage the hive infestation. However, the repeated and possibly incorrect use of acaricide treatments, as tau ‐fluvalinate, has led to the development of resistance. The in vitro phenotypic test allows the proportion of susceptible or resistant individuals to be known following an exposure to an active substance. In Varroa mites, resistance to tau ‐fluvalinate is associated with the presence of mutations at the position 925 of the voltage‐gated sodium channel (VGSC). RESULTS: Here, we compared the results obtained with an in vitro phenotypic test against tau ‐fluvalinate and those obtained with an allelic discrimination assay on 13 treated and untreated Varroa populations in France. The correlation between the phenotype and the genetic profile rate is found to be 0.89 Varroa mites having resistant phenotypic profile have a probability of 63% to present the L925V mutation (resistance detection reliability). However, 97% of the Varroa mites having the susceptible phenotype do not present the L925V mutation (susceptible detection reliability). CONCLUSION: The L925V mutation explains most of the resistance to tau ‐fluvalinate in V. destructor in the populations tested. However, other mutations or types of resistance may also be involved to explain the survival of Varroa mites in the phenotypic test. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Phenotypic and molecular susceptibility tests are used to assess the proportion of resistant varroa mites to tau‐fluvalinate. The L925V mutation explained 92% of the resistance to the laboratory‐calculated lethal concentration to kill 90% of the susceptible mite population (LC90). The molecular and phenotypic test could be both used to detect tau‐fluvalinate resistance and advise beekeepers in the choice of the treatment.